2014
DOI: 10.1111/head.12286
|View full text |Cite
|
Sign up to set email alerts
|

Triptan Education and Improving Knowledge for Optimal Migraine Treatment: An Observational Study

Abstract: Background It is generally felt that patient education and patient knowledge regarding triptan use for acute migraine management is important for successful and safe treatment. It is unclear how knowledgeable triptan users are regarding their triptan, how much education occurs when triptans are prescribed, and the impact patient education has on actual patient knowledge regarding triptan use. Objective The primary objective was to compare triptan users’ self-perceived knowledge and actual knowledge about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Guidelines for acute treatment therefore stress the importance of ensuring that patients understand the condition and their treatment strategy, and that acute therapy be taken early in attacks [4,5]. Education initiatives may therefore help to minimize ineffective use of acute therapies and associated healthcare resource use (e.g., ED visits) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for acute treatment therefore stress the importance of ensuring that patients understand the condition and their treatment strategy, and that acute therapy be taken early in attacks [4,5]. Education initiatives may therefore help to minimize ineffective use of acute therapies and associated healthcare resource use (e.g., ED visits) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the aforementioned 'in-App' incentivisation approach [18], directed education of migraine patients concerning digital headache diary App capabilities may further improve take up and compliance. Amongst triptan users, researchers observed that those migraine patients who had previously received education on this family of medications did have better knowledge around their correct use [21]. Finally, in terms of clinicians potentially using digital headache diaries as part of management plans, a more selective approach to which migraine patients are offered an App may be one option.…”
Section: Discussionmentioning
confidence: 99%
“…An overwhelming majority of scientists see the public's limited scientific knowledge as a problem for science [26] ; however, more knowledge may represent a less perceived benefit of testing and detailed information about genetic tests may result in concern and ambivalence unlike in other diseases, where the knowledge about a specific treatment implies a greater adherence to the therapy [27][28][29] .…”
mentioning
confidence: 99%